Sentencing Domestic Violence Offenders: A Vignette Study of Public Perceptions - Horstman, Nicole J. (Journal of interpersonal violence, 2021)
This study examined public perceptions of sentencing severity for males convicted of domestic violence assault compared with non-domestic violence assault. Over the years, surveys have reported changes in community attitudes toward seeing domestic violence as a more serious issue and an increased understanding of what acts constitute a domestic violence offense (Carlson & Worden, 2005). This study aimed to (a) examine whether public perceptions of sentencing severity differ between domestic and non-domestic violence assault offenses committed under similar circumstances; and (b) whether these perceptions remain after adjusting for personal attitudes, victimization experiences, and sociodemographic factors. After reading vignette scenarios depicting domestic and non-domestic assault, 284 undergraduate students responded to a survey about their perceptions of appropriate sentence outcomes and length. Results found that regardless of participants’ punitiveness (and other factors), the manipulation of the victim–offender relationship was a significant predictor for judgments of sentencing severity. Notably, the results highlighted a leniency effect in the perceptions of participants toward perpetrators of domestic violence when compared with those who received the non-domestic violence scenario. These findings imply that undergraduate students judge domestic violence as less serious and hence not warranting as severe sentencing as non-domestic violence assault perpetrators. The study indicates that public perceptions of sentencing severity for domestic violence perpetrators are not consistent with the reported shift in public perceptions toward seeing domestic violence as a serious public issue. These findings highlight the importance of continued community education about domestic violence as well as the need to take care when considering engaging public opinion in sentencing practices for domestic violence perpetrators.